Microsurgical Reconstruction of the Jaws Using Vascularised Free Flap Technique in Patients with Medication-Related Osteonecrosis: A Systematic Review - Sacco, Roberto (Biomed Res Int, 2018)
BACKGROUND: Osteonecrosis of the jaw (ONJ) has been reported to be associated with patients receiving primarily bisphosphonate (BP) therapies. However, lately it has been documented that other medications, such as RANK ligand inhibitor (denosumab) and antiangiogenic drug, can cause ONJ. Micro-osseous-vascular reconstruction of the jaws in patients affected by medication-related osteonecrosis of the jaw represents a viable option of treatment for patients affected by stage III of the disease. However, there are still considerable doubts about the success of this procedure in the short, medium, and long term. MATERIAL AND METHODS: A multidatabase (PubMed/MEDLINE, EMBASE, and CENTRAL) systematic search was performed. Any type of studies considering human patients treated with antiresorptive and antiangiogenic drugs was considered. The aim of the research is to primarily understand the success rate of micro-osseous-vascular reconstruction in the short, medium, and long period of time. This review has also the goal of better understanding any perioperative and postoperative complications resulting from the use of the reconstruction techniques. RESULTS: Eighteen studies resulted eligible for the study. Fibula free flap is the most commonly utilised vascularised free flap reconstruction technique (80.76%). Ten out of eighteen studies reported no complications. Recurrence of osteonecrosis was registered in five cases (6.41%) after free flap reconstruction. The overall free flap success rate was 96.16%. CONCLUSIONS: Based on the limited data available in literature (Level 4 of the Oxford Evidence-based medicine scale), micro-osseous-vascular reconstruction of the jaws represents a valid treatment in patients with bisphosphonate-related osteonecrosis at stage III of the disease. However, additional data based on a larger cohort of patients are necessary to justify this type of intervention in patient affected by MRONJ.